Predictors of Response to Cardiac Resynchronization Therapy: A Prospective Cohort Study - Abreu, A (2018)
Submitted by Ana Quininha (ana.quininha@chlc.min-saude.pt) on 2018-01-31T15:20:32Z No. of bitstreams: 1 RPC 2017 417.pdf: 376272 bytes, checksum: 5130ce021414e35cadc618f1941232da (MD5)